Comparison of locomotive energy storage systems for heavy-haul operation - Spiryagin, M.; Wu, Q.; Wolfs, Peter; Sun, Y.; Cole, C. (2017)
© 2017 Informa UK Limited, trading as Taylor & Francis Group This paper modelled flywheel and battery energy storage systems for heavy-haul locomotives. Three heavy-haul trains with their traction power provided by diesel, diesel-flywheel, and diesel-battery locomotive consists were simulated on an existing railway. The diesel, flywheel, and battery locomotives have traction powers of 3100 kW, 2000 kW, and 3100 kW, respectively. Energy storages for the flywheel and battery ESSs are 500 kWh and 5000 kWh, respectively. Traction performance, fuel consumption, and emissions were compared for the three simulated trains. The results show that, compared with the diesel train, the diesel-flywheel and diesel-battery trains were 13.26% and 9.20% slower in speed, respectively. However, they decreased their fuel consumption by 12.40% and 20.65%, respectively, and consequently achieved the same percentage decreases for their respective emissions.